A construção de vídeos educativos para mediar o ensino de biologia na perspectiva da alfabetização científica no ensino médio - Silva, José Williames dos Santos (2020)
The teaching and learning process requires the teacher to use active strategies and methodologies that motivate and provide students with the development of skills and abilities that can permeate the objectives of the curricular subjects and place them in a context of protagonist with regard to the construction of the knowledge and improvement of scientific literacy. This research had as its general objective: To develop the construction of videos as a teaching strategy, generating learning and enhancing scientific literacy. The research took place in a state school in the municipality of Queimadas-PB, with the participation of twenty-three high school students and it was an exploratory, descriptive research with a quali/ quantitative approach, with predominance of qualitative aspects. Among the procedural methods of research, action research with triangulation stands out based on participant observation, pre-intervention and post-intervention questionnaires and the realization of a focus group. The students were divided into four groups, each with a theme: chemical and physical properties of water, mineral and distilled water, lactic acid fermentation and ethanol fermentation, about which they developed educational videos. For this, they dialogued through meetings, WhatsApp groups and made visits to institutions that allowed to contextualize the content covered in each of the four videos developed. The results obtained revealed that from the construction of educational videos in biology, students were able to enhance and develop indicators and increase levels of scientific literacy, improve competences and skills in other disciplines according to reports and observations. In this perspective, it is concluded that the construction of videos, constitutes as a teaching strategy capable of placing the student in the role of protagonist of his learning, when making use of active methodologies, requiring the use of scientific literacy tools, strategy that can be applied to the teaching of biology and extend to other high school subjects.